Indonesia-Singapore Strategy Cooperation Diplomacy in the COVID-19 Pandemic in Batam City - Rizqi Apriani Putri; Dhany Putra Pratama; Mahadiansar Mahadiansar; Anastasia Wiwik Swastiwi (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to determine the strategy of diplomatic cooperation between Indonesia and Singapore and have bilateral relations between Indonesia and Singapore and for researchers to understand and analyze the cooperation strategies the two countries have carried out during the COVID-19 pandemic. The method used by the author in this study was qualitative and would answer a more comprehensive phenomenon. This method was sourced from literature studies, written documents, online searches, and other relevant supporting documents that will be used as secondary data collection techniques. Cooperation between Indonesia and Singapore has been established since 1967. The COVID-19 pandemic has had an impact on both countries. Singapore, which is directly adjacent to Batam City, one of the regions in the Riau Islands, Indonesia, was affected by the COVID-19 pandemic. Almost all countries carried out various policies limiting mobility from tourists to trade. This pandemic provided new opportunities for Singapore-Indonesia, especially in Batam City, by creating a new collaboration. The strategy to increase cooperation between the two countries in tourism to investment and development is called “Three Bridges,” which consists of travel bubble bridges, infrastructure bridges, and digital bridges. The “Three Bridges” development strategy, to increase cooperation when COVID-19 hit the situation between the two countries, is a multidimensional program in the future. Singapore and Batam City have proximity in the border area of various sectors of cooperation. Thus, this pandemic can increase diplomatic cooperation between Indonesia and Singapore, which is a country that is directly adjacent and assisted by stakeholders between the two countries.